The Christmas which never came, through the strangeness of strangers, but for a boy with a book - Copas, Rebecca, 1968- (Darra, Qld. : R. Nungarrayi Copas, 2007)
"The context of cultural blending among Aboriginal Australians."--Provided by publishers.
Keywords: Literature and stories - Poetry